Matrix Metalloproteinase Mmp-2 and Mmp-9 Activities in Seminal Plasma - Nina Ayvazova; Violeta Rilcheva; Emiliana Konova; Roumen Roussev; Pavel Rashev (Journal of Biomedical & Clinical Research)
Matrix metalloproteinases (MMPs) areagroup of proteases containing Zn ions asacofactor, which are involved in degrading ofalarge number of extracellular matrix proteins, and bioactive molecules. They also playamajor role in processes such as cell proliferation, cell migration, differentiation and apoptosis. Very little is known about the expression and function of MMPs in the male reproductive tract. Occurrence of MMP-2 and MMP-9 activity in human seminal plasma has been previously reported but their origin and function are still not fully understood. The aim of this study was to examine the presence of MMP-2 and MMP-9 in normal and abnormal human sperm samples and find if any correlation existed between the levels of expression of MMPs and fertilization potential of the spermatozoa. Human spermsamples were examined for the presence of MMP-2 and MMP-9 by gel zymography and western blot analysis. A DNAfragmentation test was performed. The samples were divided into two groups - samples with normozoospermia and teratozoospermia. The gelatin zymography showed gelatinolytic bands with molecular weight 64 and 72 k Da corresponding to active and inactive form of MMP-2. MMP-9 was not detected. The MMP-2 enzymatic activity appeared to be much higher in samples with compromised sperm morphology as compared to the normozoospermic samples. The mean DNAfragmentation index (DFI) of the group with teratozoospermia was relatively higher (22.16%) and over the upper reference limits, compared to the normozoospermic group, in which it was within the normal range (17.26%).